What predicts university students’ entrepreneurial intentions? A contribution to the Theory of Planned Behaviour - Popov, Boris; Mijatović, Dušanka; Matanović, Jelena (Psihološka istraživanja, 2023)
The aim of the study, stemming from the Theory of Planned Behavior, was to examine the possibility of predicting the entrepreneurial intention of university students based on its motivational antecedents (perceived behavioral control and attitude towards entrepreneurship), individual entrepreneurial orientation and perception of the entrepreneurial ecosystem. The sample consisted of 217 students from universities in the territory of the Republic of Serbia from all levels of study (73.3% females). The levels of entrepreneurial intention and its motivational antecedents were assessed with the Entrepreneurial Intention Questionnaire. The individual entrepreneurial orientation scale was used to assess the entrepreneurial orientation. A scale developed within the GEM model was used to assess government and cultural support for entrepreneurship, while university entrepreneurship support was measured using a scale constructed for the purposes of this study. The results showed that entrepreneurial intention can be predicted by a positive attitude towards entrepreneurship, as well as perceived behavioral control, while individual entrepreneurial orientation was not related to entrepreneurial intention. Subjective norms showed a low but significant negative relationship with entrepreneurial intention. The role of the entrepreneurial ecosystem in predicting entrepreneurial intention is not clear and requires further study.